2023
DOI: 10.3390/polym15030597
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun Co Nanoparticles@PVDF-HFP Nanofibers as Efficient Catalyst for Dehydrogenation of Sodium Borohydride

Abstract: Metallic Co NPs@poly(vinylidene fluoride-co- hexafluoropropylene) nanofibers (PVFH NFs) were successfully synthesized with the help of electrospinning and in situ reduction of Co2+ ions onto the surface of PVFH membrane. Synthesis of PVFH NFs containing 10, 20, 30, and 40 wt% of cobalt acetate tetrahydrate was achieved. Physiochemical techniques were used to confirm the formation of metallic Co@PVFH NFs. High catalytic activity of Co@PVFH NFs in the dehydrogenation sodium borohydride (SBH) was demonstrated. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…Furthermore, it is also observed that when Ar.HBP-3 content is raised further, the β -phase proportion is lowered. Increasing the amount of Ar.HBP-3 over 10 wt.% induces agglomeration as well as inhibiting the mobility of PVDF chain links, which may help explain this phenomenon [ 57 ]. As a result of Ar.HBP-3 aggregation at the interface, induced charges migrate longitudinally and eventually neutralize the charges in the fiber, which lowers the polarizability of PVDF nanofibers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it is also observed that when Ar.HBP-3 content is raised further, the β -phase proportion is lowered. Increasing the amount of Ar.HBP-3 over 10 wt.% induces agglomeration as well as inhibiting the mobility of PVDF chain links, which may help explain this phenomenon [ 57 ]. As a result of Ar.HBP-3 aggregation at the interface, induced charges migrate longitudinally and eventually neutralize the charges in the fiber, which lowers the polarizability of PVDF nanofibers.…”
Section: Resultsmentioning
confidence: 99%
“…It is claimed that, in comparison with its as-cast film, PVDF nanofibers produced by the electrospinning technique exhibit a greater coefficient of piezoelectricity and higher energy conversion efficiency [ 5 , 6 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. Some of the positive outcomes of obtaining electrospun fibers are higher surface area-to-volume ratio, availability of diversified polymeric materials, combination of the materials’ flexibilities, comparatively lesser manufacturing expenses and ease in depositing fibers on various types of substrates [ 52 , 53 , 54 , 55 , 56 , 57 , 58 ].…”
Section: Introductionmentioning
confidence: 99%
“…54 Subsequently, hydroxyl radicals were generated through oxidizing water molecules by the photogenerated holes. Notably, the AB molecule containing a B-N coordination bond is an electron donor-acceptor complex, 57,58 implying that the B-N bond is weaker than the covalent bond. It is well known that during AB hydrolytic dehydrogenation over metal NPs, AB was adsorbed onto metal NPs to be activated, and thus the B-N bond was disrupted by the attack of water molecules to release hydrogen.…”
Section: Photocatalytic Dehydrogenation Of Abmentioning
confidence: 99%
“…However, due to their scarce availability and high cost, it has become of the utmost importance to investigate their substitute catalysts that are cheap and have the potentials to accelerate reaction rates while simultaneously reducing threshold activation energies. Thus, researchers are now focusing increasingly on abundant earth metals, such as transition metals like copper, cobalt, and nickel that are capable of catalyzing the dehydrogenation process of SBH [10][11][12].…”
Section: Introductionmentioning
confidence: 99%